This theorem is equivalent to:
(a + b)2 = a2 + 2⋅a⋅b + b2
Here is a visualization of the theorem:
The area of the orange square is
a ⋅ a
The area of the blue rectangle is:
a ⋅ b
The area of the green square is
b ⋅ b
Then, the total area of 1 orange square, 2 blue rectangles, and 1 green square is:
(a ⋅ a) + 2 ⋅ (a ⋅ b) + (b ⋅ b)
The graph shows that we can arrange the 4 rectangles into a larger square. The side of this larger square is a + b. Therefore, the area of the larger square is:
(a + b) ⋅ (a + b)
The two areas are equal, so we claim that:
(a ⋅ a) + 2 ⋅ (a ⋅ b) + (b ⋅ b) = (a + b) ⋅ (a + b)
This theorem can also be proved fairly easily using the distributive property, as shown below.
Quiz (1 point)
- a ⋅ (b + c) = (a ⋅ b) + (a ⋅ c)
- (b + c) ⋅ a = (a ⋅ b) + (a ⋅ c)
- (a + b) ⋅ c = (a ⋅ c) + (b ⋅ c)
- (a + b) + c = a + (b + c)
- a + a = a ⋅ 2
if the following are true:
- a = b
- c = d
then a + c = b + d
if the following are true:
- a = b
- b = c
then a = c
if a + b = c, then ((x + a) + b) + y = (x + c) + y
if the following are true:
- a = b
- a = c
then b = c
if the following are true:
- a = b
- b = c
then a = c
Please write your proof in the table below. Each row should contain one claim. The last claim is the statement that you are trying to prove.